Acidity Level of Broiler Meat at the Chicken Slaughterhouse in North Sinjai District - Marwatiah; Syamsul Alam; Mangalisu, Azmi (Litbang PEMAS Universitas Islam Lamongan, 2024)
This research aims to determine the acidity level of broiler meat at the chicken slaughterhouse in North Sinjai District. This research was carried out using the Completely Randomized Design (CRD) method with treatment P1 at Chicken Slaughterhouse A, P2 at Chicken Slaughterhouse B and P3 at Chicken Slaughterhouse C. The parameters observed in this study were the pH value and total titrated acid. The research results in this study were that the pH value at location A was 6.40, location B was 6.44 and location C was 6.39, Total Titrated Acid (TAT) at location A was 0.65, location B was 0.45 and location C is worth 0.86. The conclusion from the results of this research is that the acidity level of broiler meat in the three locations in the North Sinjai District chicken slaughterhouse means it can be concluded that the meat in the chicken slaughterhouse complies with the Indonesian National Standards, and has a broiler meat acidity level within the normal range.